The biomass of the medicinal red algae (Rhodophyta) in the intertidal zone of the Chabahar coasts - B.M. Gharanjik email ; M. Wynne; Xia Bangmei; S. Khajeh; H. Keyanmehr; M.R. Hosseini (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2011)
Monthly sampling of red algae was carried out from April 2005 to March 2006 in Chabahar coasts (southestern of Iran) along Sistan & Baluchistan province coastal waters. We considered monthly periods of maximum tide according to tide tables. Then seaweed growth area in intertidal zones was determind through GPS, GIS and satellite imagery. Monthly sampling was conducted on a number of transects with equal distance and in randomly chosen 50Ã50cm quadrates. The samples were transfered to Offshore Waters Research Centerâs lab and after cleaning and separating, the weight of each species recognized was measuerd according to the present references. The biomass of each species was obtained per area unit and in the total area after determing the average weight of species. During this research, 13 species of medicinal red algae were recognized, and the most important families included: Gelidiaceae, Gracilariaceae, Hypneaceae and Rhodomelaceae. Total biomass in the area of Chabahar Coasts were 865.2 tons and the monthly average was 72.1 tons. The maximum biomass was obtained in February as 149.8 tons (828g/m2) and the minimum biomass was seen in May as 16.3 tons (90.2g/m2). The maximum biomass belonged to Gracilaria corticata (%33.1) and the minimum biomass to Hypnea pannosa (%1).